Perceived customer satisfaction on Perusahaan Otomobil Kedua Sdn Bhd (PERODUA) products and services / Nurul Asyiqin Saadun - Saadun, Nurul Asyiqin (Faculty of Business and Management, 2008)
In the fiercely competitive arena such as automotive industry, it is common sense that the vehicle manufacturers seek features for their new models that would enable them to stand out from those of their rivals. This research is about a study on perceived customer satisfaction on PERODUA products and services towards product quality, product features, product design and customer service in order to better understand customers' perception. The objectives of this research is to identify the current level of customer satisfaction, to identify the relationship between variables, to determine the difference in satisfaction customers have on PERODUA products and services and lastly to provide recommendation on products and services improvement. The questionnaires are being distributed to 50 users of PERODUA products and services. The data obtained using two methods that are primary and secondary data. Once the necessary data has been collected, the data were being analyzed and summarized in a readable and easily interpretable form using the Statistical Package for the Social Science (SPSS) version 15.0. The results are in the form of reliability testing, frequency, cross-tabulation and correlation. From the findings, the conclusion can be made whether customers are satisfied with the product quality, product features, product design and customer service of PERODUA and to provide recommendations based on findings.